Peningkatan Hasil Belajar IPA Melalui Model Pembelajaran Kooperatif Tipe Send-A-Problem di Sekolah Dasar: Penelitian Tindakan Kelas Pada Materi Sumber Daya Alam Siswa Kelas IV SDN 41 Pekanbaru - Liswan Habibi; Joni Joni (LPPI Yayasan Almahmudi bin Dahlan, 2023)
This research is motivated by the low learning result of science at the four year students of state elementary school 41 Pekanbaru. One of solution to solve this problem by implementation of cooperative learning model the type of Send-A- Problem. The objective of study to know increase learning result of science at the IV year students of state elementary school 41 Pekanbaru by implementation of cooperative learning model the type of Send-A-Problem. This research is a kind of Classroom Action Research executed in two cycles. Every cycles consisted of bay one meeting and four phase, thas is planning, action, observation, and reflection. the subjects in this research is the teachers, fourth grade students of 41 Pekanbaru the number of students of 36 people, consisting of 12 men and 13 women. Data collection techniques used in this study is the observation, testing, and documentation. Having conducted research note an increase in student learning outcomes of prior actions, the first cycle and second cycle. In the pre-action mastery students only reached 47.22% or 17 students who completed, the students who pass the first cycle increased to 24 people or completeness only reached 66,67%. In the second cycle turns completeness students at 32 students or the percentage of 88,89%. Thereby that is the implementation of cooperative learning model the type of Send-A-Problem to increase learning result of science at the four year students of state elementary school 41 Pekanbaru